Penegakan Hukum Terhadap Pelaku Balap Liar Yang Dilakukan Oleh Anak Dibawah Umur Di Wilayah Hukum Kepolisian Resor Kota Pekanbaru Berdasarkan Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan. - Gilbranu, Dimo; Effendi, Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Children are the generation and potential of the nation in pebangunan to realize the ideals of independence. The main cause of the rampant delinquency of children under the age of today is due to lack of attention and affection of parents. One of the delinquency of children is a criminal act of wild racing, wild racing is a lot happening in the city of Pekanbaru especially during the night of the week.The formulation of the problem in this research there are two, first, how law enforcement against wild racing perpetrators conducted by minors in the jurisdiction of city police resort Pekanbaru based on law number 22 of 2009 on traffic and road transport ?. Secondly, what are the obstacles faced in law enforcement against illegal racing perpetrators by minors in the municipal police resort area Pekanbaru based on law number 22 of 2009 on traffic and road transport ?.The conclusions of this research are two, namely first, law enforcement against wild racing perpetrators conducted by minors in the jurisdiction of resort police resort Pekanbaru city based on law number 22 of 2009 on traffic and road transport. Law enforcement against wild racing by children under age in the city of Pekanbaru by the traffic police unit using two ways that is preventive, and repressive. Second, obstacles faced in law enforcement against illegal racing perpetrators by minors in the municipal police resort area Pekanbaru based on law number 22 of 2009 on traffic and road transport. there are two barriers namely the general obstacles: a. The legal factor itself, b. Law enforcement factors, c. Factors of facilities or facilities that support law enforcement, d. Community factors that include legal awareness and legal compliance, and e. Factor of legal culture. The five obstacles are still making rampant wild racing conducted by children in the city of Pekanbaru.Keyword: Law Enforcement-Illegal Street Racing-Child